The Effect of Destination Image on Revisit Intention with Visitor Satisfaction as an Intervening Variable at Balaputra Dewa Museum - Hadiwijaya, Hendra (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study was to determine The Effect of Destination Image on Revisit Intention with Visitor Satisfaction as an Intervening Variable at Balaputra. The samples taken in this study were 150 Balaputra Dewa Museum visitors with simple random sampling. The results showed that there was a significant relationship between Destination Image, Visitor Satisfaction, and Interest in Revisit Intention at the Balaputra Dewa Museum. Positive Destination Image affects the level of Visitor Satisfaction, and high Visitor Satisfaction contributes to visitor intention to return to visit the museum in the future. These findings emphasize the importance of building a positive destination image and providing a satisfying experience for visitors. A good destination image creates a positive impression on visitors and increases their level of satisfaction, which in turn triggers an intention to return